Design of a secure and efficient multiple coins plus multiple denominations e-cash scheme - Chang, Yu Cheng (2004)
Anonymous electronic cash (E-Cash) are inefficient compared to other electronic payment systems, since the additional â€œanonymousâ€ functionality increases the complexity and processing time. Thus, the objective of this thesis is to address and improve the efficiency of E-Cash. A Modified Batch Signature Generation Concept has been devised and implemented into Brandâ€™s model. The resultant multiple coins scheme proved to be more efficient than many existing schemes. Further efficiency improvement was achieved by implementing preprocessing, on-line and post-processing concept. Then, multiple denominations functionality was added to the scheme which further improved the efficiency. After that, coin tracing and owner tracing functionality has been included using New Indirect Discourse of Proof which is more efficient than previous method. The security analysis has been performed on Brandâ€™s model/scheme found some lapses in his scheme such that it is vulnerable to some form of attacks. Since Brandâ€™s scheme is the basis of most E-Cash schemes including the scheme developed in this research, this discovery is significant. Improvements were then made to the scheme that has been developed to make it secure from these attacks. The resultant scheme is called Changâ€™s scheme. Comparison of Changâ€™s scheme with other â€œstate of the artâ€ E-Cash schemes showed that Changâ€™s scheme is better, if observed from both efficiency and security perspective.